Caffeine improves bladder function in streptozotocin‐induced diabetic rats. Issue 1 (9th November 2018) - Liu, Ya‐Dong; Zhang, Si‐Cong; Xue, Jun; Wei, Zhong‐Qing; Shen, Bai‐Xin; Ding, Liu‐Cheng
Abstract : Aims: To examine the protective effects of caffeine in rats with diabetes mellitus (DM) by using urodynamics. Methods: Female Sprague‐Dawley rats ( n  = 24) were divided into four groups: control group, DM group, DM + caffeine (5 mg/kg/day), and DM + caffeine (10 mg/kg/day). DM was induced by streptozotocin (STZ). Cystometric studies were conducted on all rats. After 8 weeks of treatment with caffeine, the urodynamic parameters, including bladder capacity, residual urine volume, voiding time, and peak voiding pressure, were measured. Results: DM rats had a higher bladder capacity and post‐void residual urine volume (PVR), an increased voiding time and peak voiding pressure, and a markedly lower voiding efficiency than the control group rats. After treatment with caffeine, bladder capacity, post‐void residual urine volume, and peak voiding pressure were significant lower than those in the DM group, but voiding efficiency was markedly higher. Conclusion: The results suggested that caffeine (5 or 10 mg/kg/day) may improve the bladder function at 8 weeks after STZ induction. Thus, this may represent a potential strategy to increase voiding efficiency in diabetes.